2021
DOI: 10.15252/embj.2021108883
|View full text |Cite
|
Sign up to set email alerts
|

CRYPTOCHROMES promote daily protein homeostasis

Abstract: The daily organisation of most mammalian cellular functions is attributed to circadian regulation of clock-controlled protein expression, driven by daily cycles of CRYPTOCHROME-dependent transcriptional feedback repression. To test this, we used quantitative mass spectrometry to compare wild-type and CRY-deficient fibroblasts under constant conditions. In CRY-deficient cells, we found that temporal variation in protein, phosphopeptide, and K + abundance was at least as great as wild-type controls. Most strikin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 148 publications
(259 reference statements)
1
27
0
Order By: Relevance
“…Consistent with similar previous studies, <10% of detected proteins showed any significant variation over the circadian cycle (Fig 2E). This is also expected considering the long average half-life (∼days) of mammalian proteins (Mathieson et al , 2018; Schwanhäusser et al , 2011; Wong et al , 2022). Amongst those with significant temporal variation, we found that similar proportions of the proteome showed rhythms in synthesis as rhythms in abundance (Fig 2E).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Consistent with similar previous studies, <10% of detected proteins showed any significant variation over the circadian cycle (Fig 2E). This is also expected considering the long average half-life (∼days) of mammalian proteins (Mathieson et al , 2018; Schwanhäusser et al , 2011; Wong et al , 2022). Amongst those with significant temporal variation, we found that similar proportions of the proteome showed rhythms in synthesis as rhythms in abundance (Fig 2E).…”
Section: Resultssupporting
confidence: 53%
“…Over two days under constant conditions we observed a significant ∼24h oscillation in proteasomal trypsin-like and chymotrypsin-like activities of the proteasome, but not caspase-like activity (Fig 1C). Moreover, we detected a significant interaction between genotype and biological time when comparing trypsin-like proteasome activity between wild type and Cryptochrome1/2-deficient cells, that lack canonical circadian transcriptional feedback repression (Fig S1B, (Wong et al , 2022)). Previous proteomics studies under similar conditions have revealed minimal circadian variation in proteasome subunit abundance (Wong et al , 2022), suggesting that proteasome activity rhythmicity, and therefore rhythms in UPS-mediated protein degradation, are regulated post-translationally (Marshall & Vierstra, 2019; Hansen et al , 2021).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, multi‐omic analyses have demonstrated a weak overlap between rhythmic gene transcripts and their encoded proteins, challenging the widely accepted view that timing instructions proceed linearly from transcription to translation 19,20 . Interestingly, core clock proteins have been shown to act post‐translationally to regulate protein synthesis and improve robustness of circadian outputs 21,22 …”
Section: The Circadian Clockmentioning
confidence: 99%
“…19,20 Interestingly, core clock proteins have been shown to act post-translationally to regulate protein synthesis and improve robustness of circadian outputs. 21,22 Whilst the search continues for a communicating factor between classic TTFLs and non-TTFL mechanisms of circadian regulation, these data provide insight to the layers of complexity within circadian systems and encourages researchers to consider non-TTFL mechanisms driving circadian observations, especially in cases where canonical clock gene homologues have yet to be identified, such as in most parasites.…”
mentioning
confidence: 99%